Quantum Computing Encryption: Emerging Trends in Cybersecurity - Vishnuvardhana Reddy Veeraballi (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the emerging trends in cybersecurity in response to the advent of quantum computing, focusing on the development of quantum-safe encryption methods. It begins by examining the vulnerabilities of traditional encryption algorithms like RSA and ECC to quantum attacks, particularly through Shor’s algorithm. The article then delves into post-quantum cryptography (PQC), discussing key approaches such as lattice-based cryptography, hash-based signatures, and code-based cryptography, along with their advantages and challenges. Quantum Key Distribution (QKD) is explored as an alternative method for secure communication, leveraging quantum mechanics principles. The article also covers the ongoing standardization efforts led by organizations like NIST, highlighting the progress made in establishing quantum-resistant algorithms and the challenges in their widespread adoption. Finally, it addresses the future-proofing of encryption systems, discussing the balance between quantum resistance and current security needs, the maintenance of confidentiality, integrity, and authentication, and potential hybrid approaches. Throughout, the article emphasizes the critical nature of these developments in ensuring long-term data security in a world where quantum computers may soon become a reality.